Rabies encephalitis in a child: a failure of rabies post exposure prophylaxis?. (14th January 2015) - Tinsa, Faten; Borgi, Aida; Jahouat, Imen; Boussetta, Khadija
Abstract : Rabies remains a serious public health problem in many developing countries. The diagnosis is easy when a non-immunised patient presents with hydrophobia and hypersalivation after a bite by a known rabid animal but more difficult when a patient presents atypical symptoms after having received rabies postexposure prophylaxis. Rabies postexposure prophylaxis failure is rare. We report a case of a 6-year-old boy who presented febrile seizure with agitation and cerebellar signs, without hydrophobia or hypersalivation, 17 days after a dog bite. Despite four doses of rabies vaccine and immunoglobulin, he died. Diagnostic confirmation of rabies encephalitis was made in post mortem on brain biopsies by fluorescent antibody technique.